Analysis on the effects of ecological conservation redline policies in the Pearl River Delta area, China - Xin Wang; Zhe Zhang; Haiguang Hao; Chao Zhang; Ding Wang (Frontiers in Ecology and Evolution, 2023)
IntroductionThe ecological conservation redline (ECR) policies conducted in China are an important innovation to protect biodiversity, safeguard ecological security, and achieve sustainable development. The Pearl River Delta (PRD) area implemented the ECR policies in 2005.MethodsThis study examines the contrast between the 15 years before and after 2005. It also reveals the ECR policies' effects by comparing land use change, landscape pattern index, and habitat quality inside (IECR) and outside (OECR) the ECR area. Results and discussionThe results suggest that: (1) The ECR area has served as an ecological barrier in maintaining the stability of natural ecosystems. Over the past 30 years, the PRD area significantly changed land use types and ecosystems, mainly concentrated in the central plains and estuaries. Specifically, in the IECR, land use change was relatively stable, with a decrease of 0.05% and 0.57% in ecological land and an increase of 0.28% and 0.68% in construction land before and after 2005. In contrast, the OECR area land use changed dramatically, with a decrease of 0.37% and 1.36% in ecological land and an increase of 7.06% and 5.02% in construction land before and after 2005. (2) A general trend of landscape fragmentation exists in the study area. The contagion (CONTAG) in the IECR area is higher than in the OECR. The Shannon's diversity index (SHDI) in the IECR is lower than in the OECR area, which indicates a high degree and rapid landscape fragmentation in the OECR area. (3) Over 85% of the IECR scale had a habitat quality of 0.8–1, while the OECR area had an almost half scale with a habitat quality of 0–0.2. On the whole, the ecological stability and landscape connectivity of in the IECR area was higher than that of the OECR area. This indicates that the prohibitions on human disturbance, industrial construction, and logging activities in the IECR area allow green vegetation to succumb under natural conditions. Habitat quality in the IECR area was also higher than that of the OECR area in the PRD area, revealing that the quality of green development in the IECR area was higher. Finally, the ECR policies’ implementation has protected the environment in the PRD area and will provide experience for ecological conservation in other areas.